Structure, Function and Protein Engineering of Cereal-Type Inhibitors Acting on Amylolytic Enzymes - Møller, Marie Sofie; Svensson, Birte (Frontiers in Molecular Biosciences, 2022)
Numerous plants, including cereals, contain seed proteins able to inhibit amylolytic enzymes. Some of these inhibitors, the CM-proteins (soluble in chloroform:methanol mixtures) – also referred to as cereal-type inhibitors (CTIs) – are the topic of this review. CM-proteins were first reported 75 years ago. They are small sulfur-rich proteins of the prolamine superfamily embracing bifunctional α-amylase/trypsin inhibitors (ATIs), α-amylase inhibitors (AIs), limit dextrinase inhibitors (LDIs), and serine protease inhibitors. Phylogenetically CM-proteins are predicted across poaceae genomes and many isoforms are identified in seed proteomes. Their allergenicity and hence adverse effect on humans were recognized early on, as were their roles in plant defense. Generally, CTIs target exogenous digestive enzymes from insects and mammals. Notably, by contrast LDI regulates activity of the endogenous starch debranching enzyme, limit dextrinase, during cereal seed germination. CM-proteins are four-helix bundle proteins and form enzyme complexes adopting extraordinarily versatile binding modes involving the N-terminal and different loop regions. A number of these inhibitors have been characterized in detail and here focus will be on target enzyme specificity, molecular recognition, forces and mechanisms of binding as well as on three-dimensional structures of CM-protein–enzyme complexes. Lastly, prospects for CM-protein exploitation, rational engineering and biotechnological applications will be discussed.